2017
DOI: 10.1136/bmjopen-2017-016127
|View full text |Cite
|
Sign up to set email alerts
|

Workforce characteristics and interventions associated with high-quality care and support to older people with cancer: a systematic review

Abstract: ObjectivesTo provide an overview of the evidence base on the effectiveness of workforce interventions for improving the outcomes for older people with cancer, as well as analysing key features of the workforce associated with those improvements.DesignSystematic review.MethodsRelevant databases were searched for primary research, published in English, reporting on older people and cancer and the outcomes of interventions to improve workforce knowledge, attitudes or skills; involving a change in workforce compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Nurses need the education and support from nursing and organizational leadership to provide high quality oncology nursing care for older adults. Surveys of geriatric oncology nursing knowledge suggests there are currently gaps in education regarding geriatric screening, comprehensive geriatric assessment, and supporting older adults with cancer that need to be addressed [19,21,22,75,76]. One of the biggest barriers to implementing geriatric oncology care for older adults with cancer is the lack of resources such as time [58].…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Nurses need the education and support from nursing and organizational leadership to provide high quality oncology nursing care for older adults. Surveys of geriatric oncology nursing knowledge suggests there are currently gaps in education regarding geriatric screening, comprehensive geriatric assessment, and supporting older adults with cancer that need to be addressed [19,21,22,75,76]. One of the biggest barriers to implementing geriatric oncology care for older adults with cancer is the lack of resources such as time [58].…”
Section: Rationalementioning
confidence: 99%
“…Rationale: There is a shortage of evidence related to providing high quality cancer care to older adults with cancer and their caregivers, and how to support them during and after their treatments. Such evidence is urgently needed to improve clinical care and patientcentered outcomes [10,75].…”
Section: Rationalementioning
confidence: 99%
“…Palliative care is lacking in nursing curricula (Paice et al, ); 75% of nurses working in Japanese EOL facilities for older adults reported never receiving EOL care education (Okumura‐Hiroshige et al, ). Previous studies on EOL care focused on specialised EOL care education, mainly for cancer (Bakitas et al, ; Bridges, Lucas, Wiseman, & Griffiths, ), advanced chronic diseases (Phongtankuel et al, ), and advanced dementia (Raymond et al, ). Since older people receiving EOL care may have multiple diseases, nurses must understand various symptoms’ causes and use multiple assessment and care techniques (Bridges et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on EOL care focused on specialised EOL care education, mainly for cancer (Bakitas et al, ; Bridges, Lucas, Wiseman, & Griffiths, ), advanced chronic diseases (Phongtankuel et al, ), and advanced dementia (Raymond et al, ). Since older people receiving EOL care may have multiple diseases, nurses must understand various symptoms’ causes and use multiple assessment and care techniques (Bridges et al, ). For example, older cancer patients might have difficulty communicating because of dementia or impaired motor function (Monroe et al, ); nurses must utilise their communication knowledge and symptom assessment for appropriate pain assessment.…”
Section: Introductionmentioning
confidence: 99%
“…1 In recent years, many countries have experimented on community participation by involving community health volunteers (CHVs) to expand their health systems. 2,3 There is ample evidence to prove that CHVs can improve access to primary health care, especially among underdeveloped and developing nations. [4][5][6] CHVs can be defined as members who hail from the same locality, has an in-depth understanding of the community structure, language, and existing social beliefs nominated by the community through an active participatory process.…”
mentioning
confidence: 99%